2017
DOI: 10.7759/cureus.1107
|View full text |Cite
|
Sign up to set email alerts
|

Association of Non-alcoholic Fatty Liver Disease with Conduction Defects on Electrocardiogram

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a leading cause of liver disease in developed countries. The association of NAFLD with conduction defects is unknown. The aim of our study was to find whether an association exists between conduction defects and NAFLD.Methods: This is a case-control retrospective study of 700 patients admitted to Orange Park Medical Center, Orange Park, Florida from 2009 to 2015. Patients with a history of alcohol use, congenital heart disease, infiltrative malignancy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…One article was excluded due to the presence of alcoholic hepatic steatosis and another one was excluded as the full article was not found. We finally analysed 20 papers [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One article was excluded due to the presence of alcoholic hepatic steatosis and another one was excluded as the full article was not found. We finally analysed 20 papers [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…The two studies evaluating QTc interval in NAFLD, both being rated as "good" supported that prolonged QTc interval is independently associated with the severity of NAFLD [22,24]. Moreover, out of the fours studies that evaluated cardiac conduction abnormalities in NAFLD and supported this association, two were rated as "good" [13,14], one was rated as "fair" [27], and one as "poor" [18]. Furthermore, IHD findings evaluated by ECG in NAFLD patients was evaluated in two studies.…”
Section: Supplementary Table I Nhlbi Quality Assessment Tool For Obsmentioning
confidence: 92%
See 2 more Smart Citations
“…In particular, several epidemiological studies have suggested that NAFLD is strongly associated with an increased risk of permanent atrial fibrillation, heart rate-corrected QT interval prolongation and ventricular tachyarrhythmias both in patients with and without T2DM [ 8 13 ]. To date, only one retrospective case-control study has ascertained the association between NAFLD and heart block, demonstrating that NAFLD is closely associated with the presence of cardiac conduction defects in a hospital-based sample of 700 adult patients (about 30% of them had known T2DM) admitted to the Orange Park Medical Center in Florida from 2009 to 2015 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%